2016
DOI: 10.3390/ijms17122032
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Attenuates Intestinal Barrier Dysfunction Following Intracerebral Hemorrhage in Mice

Abstract: Intestinal barrier dysfunction remains a critical problem in patients with intracerebral hemorrhage (ICH) and is associated with poor prognosis. Ghrelin, a brain-gut peptide, has been shown to exert protection in animal models of gastrointestinal injury. However, the effect of ghrelin on intestinal barrier dysfunction post-ICH and its possible underlying mechanisms are still unknown. This study was designed to investigate whether ghrelin administration attenuates intestinal barrier dysfunction in experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Evans blue (EB) is closely attached to albumin, so it is used as a common indicator for protein extravasation in inflammatory tissue injury ( Cheng et al, 2016 ). Therefore, we evaluated the intestinal microvascular permeability by EB staining and the ratio of wet-dry weight of intestinal tissues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evans blue (EB) is closely attached to albumin, so it is used as a common indicator for protein extravasation in inflammatory tissue injury ( Cheng et al, 2016 ). Therefore, we evaluated the intestinal microvascular permeability by EB staining and the ratio of wet-dry weight of intestinal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Microvascular permeability and tissue edema are the important pathophysiological characteristics of intestinal dysfunction ( Woodruff et al, 2016 ). Determination of tissue EB which is closely attached to albumin reflects inflammatory tissue injury as a method for the examination of the extent of capillary permeability ( Diao et al, 2012 ; Cheng et al, 2016 ). In addition, the ratio of wet/dry weight is also an important indicator of capillary permeability ( Nakagawa et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tight junction proteins are important as an element in the intestinal barrier in the structure of the gut–brain axis. It was shown that ghrelin, a brain–gut peptide, attenuates intestinal barrier dysfunction activating tight junction proteins zonula occludens-1 and claudin-5 after intracerebral hemorrhage in animal model [ 70 ]. Some studies demonstrate the relationship of gut microbiome changes with intestinal barrier injury through alteration of tight junction proteins.…”
Section: Pathophysiological Mechanisms Of Intestinal Barrier Insufficiency During Cvd-associated Stressmentioning
confidence: 99%
“…Intestinal biopsies from different groups (celiac patients with active disease, celiac patients in remission, non‐celiac patients with gluten sensitivity and non‐celiac controls) showed a greater increase in permeability when exposed to gliadin in the CD group with active disease and in non‐celiac patients with gluten sensitivity compared with the CD group in remission; in addition, interleukin‐10 (IL‐10) seems to play a significant role in intestinal permeability and IL‐10 deficiency increases permeability before the development of barrier mucosal inflammation . Conversely, ghrelin seems to reduce intestinal barrier damage following intracerebral hemorrhage in mice .…”
mentioning
confidence: 99%